A Finite Element Analysis of Structural Strength of Ferry Ro-Ro’s Car Deck - M. Uswah Pawara; Alamsyah Alamsyah; Rodlian Jamal Ikhwani; Ade Ray Siahaan; Andi Mursyid Nugraha Arifuddin (Universitas Negeri Padang, 2022)
Ferry Ro-Ro is a type of ship used to carry passengers and vehicles. This ship has several decks such as navigation decks, passenger decks, and car decks. The car deck is subject to a heavy load as it should accommodate vehicle loads. This study aims to conduct a finite element analysis to determine the stress and deformation experienced on the car deck of the Ferry Ro-Ro and determine the safety factor based on BKI (Indonesian Classification Bureau). The method used in this study is the Finite Element Method (FEM) which has been applied in the finite element based-applications namely Ansys Workhbench. The simulations are carried out using the software by varying the thickness of the car deck’s plate, the plate is subjected to pressure loads which are car loads accommodated by the car deck. Moreover, the fixed support is applied in the deck during the simulation. Based on the simulation results of variations of 90, 100, and 110% plate thickness. It is obtained that the smallest plate experienced maximum stress and the obtained safety factor of all plate thickness variations was satisfied the BKI Standard.